2022
DOI: 10.3389/fpsyt.2022.825460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Participation and Its Diversity, Frequency, and Type on Depression in Middle-Aged and Older Persons: Evidence From China

Abstract: BackgroundDepression is one of the greatest public health problems worldwide. The potential benefit of social participation (SP) on mental health has been widely acknowledged. Nevertheless, a few studies have used propensity score matching (PSM) to reduce the influence of data bias and confounding variables. This study explored the effect of social participation on depression among middle-aged and older Chinese persons through a PSM method, considering the frequency, type, and quantity of SP. Effects were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Engaging in socially active activities promotes social stability and reciprocal support, which improves psychological safety and lessens anxiety symptoms. The findings are corroborated by a previous study showing that social interaction improves mental health in general [28].…”
Section: Discussionsupporting
confidence: 87%
“…Engaging in socially active activities promotes social stability and reciprocal support, which improves psychological safety and lessens anxiety symptoms. The findings are corroborated by a previous study showing that social interaction improves mental health in general [28].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, some factors can serve as modifiable intervention targets. For example, more social participation both in terms of frequency and variety has been shown to have protective effects over from frailty, cognitive impairment, and depressive symptoms among Chinese older adults [59][60][61]. Given the association between social participation and the identified trajectories, engaging at-risk older adults in proper social activities may help alleviate the progression of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study from China reported that low levels of social participation were associated with elevated depressive symptoms in adults aged 50 and beyond [ 21 ]. In addition, social participation has been found to play an important role in alleviating depression [ [22] , [23] , [24] ]. Cognitive reserve theory explains individual differences in susceptibility to age-related brain changes or pathological changes associated with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%